2016
DOI: 10.1186/s13075-016-1032-z
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin and TNF trough serum levels identify power Doppler ultrasound synovitis in rheumatoid arthritis and psoriatic arthritis patients in remission or with low disease activity

Abstract: BackgroundSerum levels of calprotectin, a major S100 leucocyte protein, are associated with disease activity in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients. Higher drug trough serum levels are associated with good response in patients treated with tumour necrosis factor inhibitors (TNFi). Power Doppler ultrasound (PDUS) synovitis is predictive of flare and progression of structural damage in patients in clinical remission. The purpose of this study was to analyse the accuracy of calprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
8
29
0
1
Order By: Relevance
“…However, it is important to note that CRP forms part of the DAS-CRP and SDAI constructs, and patients satisfying the remission criteria defined by these indexes are inherently those in whom CRP failed to discriminate US-detected subclinical inflammation. Our results are in line with those published recently by Inciarte-Mundo et al who had investigated levels of serum calprotectin and its ability to identify PD synovitis in patients with RA and psoriatic arthritis in clinical remission and low disease activity treated by antiTNFα agents [28]. In contrast to above mentioned study, we have focused here more strictly only on patients in clinical remission.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is important to note that CRP forms part of the DAS-CRP and SDAI constructs, and patients satisfying the remission criteria defined by these indexes are inherently those in whom CRP failed to discriminate US-detected subclinical inflammation. Our results are in line with those published recently by Inciarte-Mundo et al who had investigated levels of serum calprotectin and its ability to identify PD synovitis in patients with RA and psoriatic arthritis in clinical remission and low disease activity treated by antiTNFα agents [28]. In contrast to above mentioned study, we have focused here more strictly only on patients in clinical remission.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we suggested that calprotectin and musculoskeletal ultrasonography might provide more reliable tools for evaluating joint inflammatory activity in RA patients. In line with our hypothesis, Inciarte-Mundo et al [28] have recently demonstrated that calprotectin and TNF trough serum levels may help to identify power Doppler ultrasound synovitis in biologic-treated patients with RA and psoriatic arthritis in remission or low disease activity.…”
Section: Introductionsupporting
confidence: 86%
“…Serum and plasma levels of calprotectin are associated with ultrasound assessments of RA disease activity,9 23 25 and elevated levels of calprotectin may indicate sustained inflammation in patients in remission or low disease activity according to DAS28 31…”
Section: Introductionmentioning
confidence: 99%
“…72 A recent study by Inciarte-Mundo et al 84 showed that CLP was associated with synovitis at the ultrasonography assessment in RA and psoriatic arthritis (PSA) patients in remission. CLP serum levels had the highest discriminatory capacity compared to CRP and ESR and a cut-off of 1.66 mg/ml for synovitis presence was also identified.…”
Section: Clp In Rheumatic Diseasesmentioning
confidence: 99%
“…CLP serum levels had the highest discriminatory capacity compared to CRP and ESR and a cut-off of 1.66 mg/ml for synovitis presence was also identified. 84 Notably, CLP is the only biomarker which has been shown to correlate with radiographic scores 48,49 and there is some evidence that baseline CLP might be predictive of radiographic damage. 48,49,85 In a recent study by Vogl et al, 86 CLP was tested as a marker of inflammation in a murine model of arthritis by optical molecular imaging.…”
Section: Clp In Rheumatic Diseasesmentioning
confidence: 99%